Optimization of a two-step CH4/air reaction mechanism in a CO2-enriched environment for high-fidelity combustion simulations - Castellani, S.; Nassini, P. C.; Andreini, A. (Frontiers in Mechanical Engineering, 2023)
In the gas turbine framework, the adoption of Carbon Capture and Storage (CCS) systems coupled with strategies to improve the exhaust CO2 content is a promising technology to abate the carbon footprint of such machines. However, any departure of the oxidant from the air can compromise the accuracy of the conventional models to represent the combustion process. In this work, the effect of the CO2 enrichment of the mixture on an atmospheric premixed swirled flame is investigated by means of LES, comparing the numerical predictions with the experimental results. The high-fidelity numerical model features a dedicated global reaction mechanism, derived through an in-house optimization procedure presented here. The chemical scheme is obtained by optimizing a widely-used CH4-air two-step mechanism to improve key flame parameters such as the laminar flame speed and thickness and the resistance of the flame to the stretch with moderate CO2 dilution. The numerical results are analysed in terms of flame shape, heat losses and pressure fluctuations, showing a promising agreement with the experimental measurements and demonstrating the capabilities of the numerical model for CO2-diluted combustion.